Computers Helping People with Special Needs : 17th International Conference, ICCHP 2020, Lecco, Italy, September 9–11, 2020, Proceedings /: 17th International Conference, ICCHP 2020, Lecco, Italy, September 9–11, 2020, Proceedings. (2020) - Unknown
No abstract available